From knife to needle – the trend of vascular neurosurgery in Belgium - Jorn Van Der Veken; Vera Van Velthoven; Gilles Reuter; Steven De Vleeschouwer; Tomas Menovsky; Johnny Duerinck; Michaël Bruneau (Brain and Spine)
Introduction: The management of neurovascular pathologies has changed globally over the last few decades. Endovascular treatments are increasing, and fewer surgical procedures are performed. Research question: Evaluate the evolution of vascular neurosurgery in Belgium over the last 30 years and compare with other countries. Material and methods: Belgian nationwide data was obtained from 1991 to 2021 via the National Institute for Health and Disability Insurance (INAMI-RIZIV). Cost of surgical and endovascular implants used in 2022 was obtained. Results: Over a 30-year period a total of 37,504 procedures were performed in Belgium, consisting of 13,767 (36.7%) surgeries and 23,737 (63.3%) endovascular treatments (EVT).Adjusted to population per 100000, surgical management peaked at 6.02 in 1996 and gradually dropped below 3.0 in 2019. EVT increased from 1.06 in 1991 to 10.5 in 2021.Important regional differences are seen in terms of total number of procedures as well as ratio of surgery to endovascular surgery.The total cost of surgical implants in 2022 was the equivalent of 1% of the total cost of endovascular implants. Discussion and conclusions: This data confirms a similar trend to other regions in the world: a reduction in surgical management and increase in endovascular management for CNS vascular pathologies.Important regional differences are noted in terms of volume and ratio of endovascular to surgery.A nationwide registry based on patient data and outcomes can help decide whether there should be centralization to manage vascular pathologies.